A General Approach for Lab‐to‐Manufacturing Translation on Flexible Organic Solar Cells. Issue 41 (18th August 2019) - Meng, Xiangchuan; Zhang, Lin; Xie, Yuanpeng; Hu, Xiaotian; Xing, Zhi; Huang, Zengqi; Liu, Cong; Tan, Licheng; Zhou, Weihua; Sun, Yanming; Ma, Wei; Chen, Yiwang
Abstract: The blossoming of organic solar cells (OSCs) has triggered enormous commercial applications, due to their high‐efficiency, light weight, and flexibility. However, the lab‐to‐manufacturing translation of the praisable performance from lab‐scale devices to industrial‐scale modules is still the Achilles' heel of OSCs. In fact, it is urgent to explore the mechanism of morphological evolution in the bulk heterojunction (BHJ) with different coating/printing methods. Here, a general approach to upscale flexible organic photovoltaics to module scale without obvious efficiency loss is demonstrated. The shear impulse during the coating/printing process is first applied to control the morphology evolution of the BHJ layer for both fullerene and nonfullerene acceptor systems. A quantitative transformation factor of shear impulse between slot‐die printing and spin‐coating is detected. Compelling results of morphological evolution, molecular stacking, and coarse‐grained molecular simulation verify the validity of the impulse translation. Accordingly, the efficiency of flexible devices via slot‐die printing achieves 9.10% for PTB7‐Th:PC71 BM and 9.77% for PBDB‐T:ITIC based on 1.04 cm 2 . Furthermore, 15 cm 2 flexible modules with effective efficiency up to 7.58% (PTB7‐Th:PC71 BM) and 8.90% (PBDB‐T:ITIC) are demonstrated with satisfying mechanical flexibility and operating stability. More importantly, this work outlines the shear impulse translation for organic printing electronics. Abstract : A general approach for lab‐to‐manufacturing translation is developed to achieve high‐performance flexible organic solar modules without obvious efficiency loss. The shear impulse during the coating/printing process is applied to control the morphology evolution of the bulk heterojunction layer for both fullerene and nonfullerene acceptor systems. A quantitative transformation factor of shear impulse between slot‐die printing and spin‐coating is detected.